Response of Conventional Sorghum to IMIFLEX, Zest WDG, and FirstAct - R. Liu; V. Kumar; M. Marrs; T. L. Lambert (Kansas Agricultural Experiment Station Research Reports, 2022)
Grass weed control in sorghum has been a serious challenge for sorghum growers. The newly developed herbicide-tolerant (HT) sorghum technologies such as igrowth, Inzen, and Double Team sorghum will allow growers to use IMIFLEX, ZestWDG, and FirstAct respectively, for in-season weed control. However, the adoption of these HT sorghum technologies may increase the use of these labeled herbicides and increase the likelihood of herbicide drift or tank contamination to conventional sorghum. Three separate field studies were conducted at Kansas State University Agricultural Research Center (KSU-ARCH) near Hays, KS, to understand the response of conventional sorghum to various rates of IMIFLEX, ZestWDG, and FirstAct applied at two different growth stages. Results indicated that field-use rates (1X) of IMIFLEX, Zest WDG, and FirstAct resulted in 90 to 100% injury and complete or near-complete grain yield loss of conventional sorghum. In addition, low rates of ZestWDG (as low as 1/50X) and FirstAct (as low as 1/10X) also caused significant injury and grain yield loss of conventional sorghum. In conclusion, these results suggested that either drift or tank-contamination of these herbicides (even at low rates) can cause significant injury or grain yield loss of conventional sorghum. Proper adherence to the stewardship guidelines are necessary to avoid the drift or tank-contamination from these herbicides to conventional sorghum.
Keywords: herbicide; herbicide-tolerant; injury; new technology; sorghum